Electromaterials for Environment & Energy Volume I - Cretin, Marc; Tingry, Sophie; Tang, Zhenghua (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
In a developing world, the demands for energy, water and the damage to our environment are constantly increasing. Electrochemistry could be a great tool to solve these problems, with an impact that could minimize or at least control damage in our environment, since the main driver of the reaction is the electron that can be produced in a sustainable manner. In electrochemical approaches of energy conversion and production, drinking water production and wastewater treatment, the material synthesis and interface characterization are key components that greatly affect a system's performance. The Special Issue "Electromaterials for Environment & Energy" proposes a set of publications that covers a range of subjects and applications related to energy, water and environmental pollution treatment, with a focus on material and interface control for process optimization.